STYLISTIC MEANS OF ACHIEVING LEXICAL ECONOMY IN ENGLISH AND UZBEK TEXTS: A COMPARATIVE STUDY - Omonov Baxtiyor, (TADQIQOTLAR, 2026)
Abstract This  article  examines  the  stylistic  means  through  which  lexical  economy  is achieved in English and Uzbek texts. Lexical economy is understood as the linguistic tendency to express complex meanings using minimal lexical and structural resources. The study analyzes stylistic devices such as ellipsis, abbreviation, metaphor, lexical substitution,  word-formation  processes,  agglutinative  morphology,  idiomatic expressions,  and  contextual  omission.  A  qualitative  descriptive  and  comparative methodology  is  employed,  based  on  data  drawn  from  literary  works,  journalistic discourse, everyday communication, and digital media in both languages. The findings demonstrate  that  English  primarily  achieves  lexical  economy  through  syntactic compression, abbreviation, and metaphorical expression, whereas Uzbek relies mainly on  agglutinative  morphology,  contextual  inference,  and  idiomatic  units.  Despite typological differences, both languages reveal a shared communicative principle of efficiency  and  expressiveness.  The  study  highlights  implications  for  translation, language teaching, and cross-linguistic communication.